2008
DOI: 10.4314/bcse.v22i3.61246
|View full text |Cite
|
Sign up to set email alerts
|

<b>Syntheses and spectral studies of novel ciprofloxacin derivatives</b>

Abstract: Reaction of 1-cyclopropyl-6-fluoro-4-oxo-7-(piperazin-1-yl)-1,4-dihydroquinoline-3-carboxylic acid (ciprofloxacin) with thiazole/benzothiazole diazonium chloride afforded piperazine substituted ciprofloxacin derivative. The acid part of these derivatives was further condensed with various β-diketones to get 1-cyclopropyl-6-fluoro-4-oxo-7-(4-(thiazol-2-yldiazenyl)piperazin-1-yl)-1,4-dihydroquinoline-3-carboxylic acid derivatives (5ae) and 7-(4-(benzo[d]thiazol-2-yldiazenyl)piperazin-1-yl)-1-cyclopropyl-6-fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The structure-activity relationship (SAR) and the functions of different positions on the quinolone core have been identified (14). The SAR studies indicated that the group at position 7 affects its antibacterial spectrum (15). The substituted 7-piperazinyl derivatives of ciprofloxacin, such as azo (11), Mannich base (16,17), N-alkylated (18) and N-acylated ciprofloxacin derivatives (19) have been synthesized and evaluated for antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The structure-activity relationship (SAR) and the functions of different positions on the quinolone core have been identified (14). The SAR studies indicated that the group at position 7 affects its antibacterial spectrum (15). The substituted 7-piperazinyl derivatives of ciprofloxacin, such as azo (11), Mannich base (16,17), N-alkylated (18) and N-acylated ciprofloxacin derivatives (19) have been synthesized and evaluated for antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by Yadev and Sharma that ciprofloxacin may form a diazotized compound upon reacting with piprazine. 17 This reaction utilizes thionyl chloride as a solvent, and takes place after a 4-h reflux. It utilizes the NH of ciprofloxacin.…”
Section: Theoretical Basis For the Microwave Assisted Diazotization Omentioning
confidence: 99%
“…16 Its reaction with piprazine forms a diazotized compound that is colored in nature. 17 The nature and extent of reactions may depend upon a number of factors, including the way of energy transfer. Among these, the microwave assisted reactions are unique regarding their speed and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Several quinolones modifications have been shown to improve properties in cancer treatment. Some modifications comprise ß-keto and carboxylic acid moiety that are required for hydrogen-bonding interactions with DNA gyrases or/and DNA bases, and therefore, both two functional group moieties are essential [6]. e proximity of the carboxyl and keto groups on the fluoroquinolone molecule would account for good chelating properties [7], suggesting that the interaction of the quinolone complexed to metal is a major step [8].…”
Section: Introductionmentioning
confidence: 99%